The Willingness to Pay for Mortality Risk Reductions: A Comparison of the United States and Canada - Anna Alberini; Alan Krupnick; Maureen Cropper; Nathalie Simon; Joseph Cook (Center for Economic Studies and ifo Institute (CESifo), 2002)
We present results for two contingent valuation surveys conducted in Hamilton, Canada and the US to elicit WTP for mortality risk reductions. We find similar Value of Statistical Life estimates across the two studies, ranging from USD 930,000 to USD 4.8 million (2000 US dollars). WTP increases with risk reduction size, but varies little with respondent age: individuals aged over 70 years hold WTP values approximately one-third lower than other respondents. Respondent health status has limited effect on WTP. These results provide little or no evidence for adjusting VSL estimates used in policy analyses for the affected population's age or health status.
Keywords: 330; value of a statistical life; mortality risks; benefit-cost analysis